Enhanced Hydrogen Storage Properties of MgH2 Using a Ni and TiO2 Co-Doped Reduced Graphene Oxide Nanocomposite as a Catalyst - Zeng, Liang; Qing, Peilin; Cai, Fangfang; Huang, Xiantun; Liu, Haizhen; Lan, Zhiqiang; Guo, Jin (Frontiers in Chemistry, 2020)
To improve the hydrogen storage properties of Mg/MgH2, a Ni and TiO2 co-doped reduced graphene oxide ((Ni-TiO2)@rGO) nanocomposite is synthesized by a facile impregnation method and introduced into Mg via ball milling. The results demonstrated that the dispersive distribution of Ni and TiO2 with a particle size of 20–200 nm in the reduced graphene oxide matrix led to superior catalytic effects on the hydrogen storage properties of Mg-(Ni-TiO2)@rGO. The initial hydrogenation/dehydrogenation temperature for Mg-(Ni-TiO2)@rGO decreased to 323/479 K, 75/84 K lower than that of the additive-free sample. The hydrogen desorption capacity of the Mg-(Ni-TiO2)@rGO composite released 1.47 wt.% within 120 min at 498 K. When the temperature was increased to 523 K, the hydrogen desorption capacity increased to 4.30 wt.% within 30 min. A hydrogenation/dehydrogenation apparent activation energy of 47.0/99.3 kJ·mol-1 was obtained for the Mg-(Ni-TiO2)@rGO composite. The improvement in hydrogenation and dehydrogenation for the Mg-(Ni-TiO2)@rGO composite was due to the reduction of the apparent activation energy by the catalytic action of (Ni-TiO2)@rGO.